DEVELOPING CRITICAL READING SKILLS THROUGH IELTS-ORIENTED TASKS IN UNIVERSITY EFL CLASSES - Inoyatova Umida Boxadir qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines how IELTS-oriented reading tasks can support the development of critical reading skills among university EFL learners. With the increasing demand for academic literacy in higher education, students must engage with texts beyond literal comprehension to evaluate arguments, infer meaning, and integrate  information  effectively.  Current  pedagogical  research  highlights  the potential  of  exam-oriented  tasks  as  tools  for  fostering  higher-order  thinking  when combined with strategic instruction. Drawing on recent studies, this article explores theoretical perspectives on task-based reading, cognitive and metacognitive strategies, and the role of reflective practice in enhancing critical reading.